LEVEL OF ZINC AND ITS FRACTIONS AS REFLECTION OF A CONDITION OF ANTIOXIDANT SYSTEM AT THE CHRONIC OBSTRUCTIVE LUNG DISEASE - V. I. Shevcova; A. A. Zujkova; A. N. Pashkov; A. N. Shevcov (SINAPS LLC, 2018)
Objective. To estimate a possibility of use of zinc and its fractions as the indicator reflecting a condition of antioxidant system at sick HOBL and persons from risk groups. Materials and methods. Patients with COPD, smokers and non-smoking healthy people have participated in a research. Everything participated in a research has carried out spirometry with definition of an indicator of FEV1 and the subsequent calculation of FEV1 % of due. Taking into account importance of the occupied role when forming COPD of an oxidative stress have been determined the level of activity of the main enzyme of antitoskidantny protection - superoxide dismutases; level of zinc and its fractions as main component of enzyme and also albumine as main tranporter of metabolic active zinc. The indicator "a share of the related fraction of zinc" for definition of changes in fractions of zinc is entered. Results of the study. It is defined that at the smoking patients with the minimum malfunction of external breath of change of indicators are similar to that at patients with COPD. Statistically significant differences in the level of the studied indicators at non-smoking patients are also revealed. With use of the correlation analysis of Spirmen reliable high correlation communications between FEV1 % from due and activity level superoxide dismutases and also between activity level superoxide dismutases and the general level of zinc and also zinc connected are defined that confirms a hypothesis of a possibility of use of level of zinc and its fractions as the indicator reflecting a condition of antioxidant system at the smoking persons at screening researches.